Antecedents and Consequences of Earnings Management: A Systematic Review of the Banking Sector in Developed and Developing Countries - Sarit Biswas; Mousumi Bhattacharya; Deepak Kumar (Australasian Accounting, Business and Finance Journal, 2024)
The accuracy and utility of financial information are critical, but the prevalent issue of earnings management (EM) casts a shade on this goal. With a growing corpus of EM literature, a comprehensive review is essential for distilling insights and guiding future research. The paper systematically reviews 182 EM studies through the distinctive lens of developing and developed country banking institutions. With an emphasis on accrual-EM, the current study thoroughly examines and synthesizes the antecedents and consequences of bank EM. Notably, certain themes (such as corporate governance, international financial reporting standards, ownership structure and liquidity) emerge as universally relevant, bridging the gap between developed and developing markets. Conversely, themes like bank efficiency, social capital, funding structure and institutional quality, among others, tend to be context-specific. Further, the study developed a conceptual framework of antecedents and consequences of bank EM by segregating them into developed, developing, and cross-country contexts. The study is unique in its developed and developing context of appraising EM literature. The results provide a better understanding of pertinent elements in diverse institutional settings that can aid regulators and policymakers in making decisions by identifying facilitators, mitigators and consequences in developed and developing economies.
Keywords: Earnings management; Bank; Literature review; Antecedents; Consequences